Multiobjective programming in optimization of interval objective functions — A generalized approach - Chanas, Stefan; Kuchta, Dorota (European journal of operational research, 1996)
We generalize known concepts (those introduced by Ishihuchi and Tanaka [1] and Rommerlfanger et al. [2]) of the solution of the linear programming problem with interval coefficients in the objective function based on preference relations between intervals. We unify all the discussed concepts as well as the corresponding solution methods into one general framework.